2001
DOI: 10.1038/sj.ijo.0801517
|View full text |Cite
|
Sign up to set email alerts
|

Decreased lipolysis and enhanced glycerol and glucose utilization by adipose tissue prior to development of obesity in monosodium glutamate (MSG) treated-rats

Abstract: OBJECTIVE:To determine the metabolic alterations that lead to the neonatal administration of monosodium glutamate (MSG), which results in arrested growth and obesity. ANIMALS AND DESIGN: Wistar rats were injected 5 times, every other day, with 4 g of MSGakg b.w. or with hyperosmotic saline (controls), within the ®rst 10 days of life, and were studied at the age of 30 days. RESULTS: Body weight was lower, whereas adipocyte lipid content, cell diameter, surface area and volume were higher in MSG rats than in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
2
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 46 publications
4
70
2
11
Order By: Relevance
“…The onset of obesity is associated with low sympathetic and high parasympathetic activities to sustain the accumulation of energy sources, such as fat tissue, decreasing catabolism, and increasing anabolism. Regarding the BW of MSG rats, we observed that they were lighter than respective control animals, which was the characteristic phenotype of this model as described by Remke et al (1988), Dolnikoff et al (2001), and Schoelch et al (2002). Although there were no overweight rats, the MSG-obese rats were found to have more fat pad stores as compared with control animals (Bernardis & Patterson 1968, Bray & York 1998, which was correlated with lower growth hormone (Bakke et al 1978, Acs et al 1982 and reduced basal metabolic rate (Arndt et al 1991).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The onset of obesity is associated with low sympathetic and high parasympathetic activities to sustain the accumulation of energy sources, such as fat tissue, decreasing catabolism, and increasing anabolism. Regarding the BW of MSG rats, we observed that they were lighter than respective control animals, which was the characteristic phenotype of this model as described by Remke et al (1988), Dolnikoff et al (2001), and Schoelch et al (2002). Although there were no overweight rats, the MSG-obese rats were found to have more fat pad stores as compared with control animals (Bernardis & Patterson 1968, Bray & York 1998, which was correlated with lower growth hormone (Bakke et al 1978, Acs et al 1982 and reduced basal metabolic rate (Arndt et al 1991).…”
Section: Discussionmentioning
confidence: 79%
“…Regarding this matter, subdiaphragmatic vagotomy (VAG) has been performed to attenuate the hyperinsulinemia in monosodium l-glutamate (MSG)-treated rats and other obese models such as Wistar fatty models (Yamatani et al 1998, Balbo et al 2000. The MSG rat is an interesting model that reconciles increased parasympathetic activity, hyperinsulinemia, and obesity, among other components of the metabolic syndrome, mimicking the disorders observed in obese individuals (Hirata et al 1997, Dolnikoff et al 2001, Karlen-Amarante et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is responsible, at least in part, for the increase of glucocorticoids found in these adult rats 16,17 . MSG can be administered subcutaneously or intraperitoneally 18,19 at doses that vary by 2-4 mg/g of body weight of the rat during the neonatal period and for periods ranging by 4-10 doses causing obesity [20][21][22][23][24] . Since MSG is a substance found in several foods consumed daily, it has been targeted by studies on its effects when taken orally.…”
Section: Monosodium Glutamate (Msg)mentioning
confidence: 99%
“…Diet A cat livers had increased expression of a number of genes related to hepatic steatosis, including DGAT1 (Millar et al 2006), perlipin (Fujii et al 2009), and fatty acid-binding protein 1. Interestingly, glycerol kinase expression was also upregulated in the livers of both MSG-containing diet groups A and C; and increased glycerol reutilization has previously been noted in the adipose tissue of MSG-treated rats (Dolnikoff et al 2001), where enhanced glycerol utilization has been suggested to contribute to the development of obesity in these animals. Glycerol can also provide a substrate for de novo hepatic TAG synthesis, during which glycerol kinase is required to convert glycerol into glycerol-3-phosphate for subsequent esterification into TAG.…”
Section: Discussionmentioning
confidence: 84%